2019
DOI: 10.18502/jad.v13i3.1542
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Leishmania major in Hemiechinus auritus, A Potential Reservoir of Zoonotic Cutaneous Leishmaniasis in Damghan, Iran

Abstract: Background: Zoonotic cutaneous leishmaniasis caused by Leishmania major is endemic in 17 of 31 Iranian provinces. Various species of rodents have been introduced as the main reservoirs of the disease. This study was conducted to de­termine the natural infection of hedgehogs with Leishmania spp. in an endemic area of the disease, northern Iran. Methods: Fifteen long-eared hedgehogs were captured alive during 18 months study period, from Apr 2015 to Sep 2016, in Damghan City, Semnan Province, Iran. The ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…This favors the use of PCR-HRM, which is characterized by very high sensitivity of detection, especially in field sampling. On the other hand, our results further corroborate previous studies that showed natural Leishmania infection of hedgehogs and suggest its potential role as a reservoir host, not only in Tunisia [9,10] but also in Algeria, where it was first described [8], and recently in Iran [7].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This favors the use of PCR-HRM, which is characterized by very high sensitivity of detection, especially in field sampling. On the other hand, our results further corroborate previous studies that showed natural Leishmania infection of hedgehogs and suggest its potential role as a reservoir host, not only in Tunisia [9,10] but also in Algeria, where it was first described [8], and recently in Iran [7].…”
Section: Discussionsupporting
confidence: 91%
“…These forms have as respective reservoirs rodents ( Psammomys and Meriones ) and gundies ( Ctenodactylus gundi ) [ 4 , 6 ]. Recently, hedgehogs were identified as potential reservoirs of L. major in Iran [ 7 ]. A few years ago, in 2014, these animals were reported to be infected by L. major in both Atelerix algirus and Paraechinus aethiopicus in Algeria [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cyber-attacks are also highly likely due to the lack of well-established computer infrastructures in the healthcare centers. In addition, Damghan is a biologically vulnerable area in terms of Cutaneous Leishmaniasis due to being home to the major resources of the disease such as rodents (26). Also, the evidence indicates an epidemic occurrence of Cutaneous Leishmaniasis in rural areas of Damghan in 2009, where on average more than 100 new cutaneous cases occur annually (27).…”
Section: Discussionmentioning
confidence: 99%
“…The city is situated between Shahroud and Semnan Cities and is bounded on the mountainous areas in the north (Alborz Mountains) with 9.8 °C and the plain areas in the south (Kaveer Desert) with 23.5 °C average temperatures. The annual rainfall and average temperature of the city are about 120mm and 16.3 °C respectively ( 21 ). The city has generally a warm weather in summer and cold in winter.…”
Section: Methodsmentioning
confidence: 99%